Renewable energy storage : its role in renewable and future electricity markets - Publishers), PEP (Professional Engineering ([S.l.] : Wiley, 2005)
It has been frequently stated that energy storage is an essential requirement if significant generation by renewables is to be achieved, but are the present systems likely to be adequate? This text reviews the present status and future potential of the different systems of energy storage, their role in power generation by renewables specifically, and the electricty market generally.